2001
DOI: 10.1152/ajpgi.2001.281.1.g216
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease is associated with changes of enterocytic junctions

Abstract: Changes of the intestinal mucosal barrier are considered to play a role in the pathogenesis of inflammatory bowel disease (IBD). Our experiments were designed to identify dysregulation of epithelial junctional molecules in the IBD intestinum and to address whether altered expression of these molecules is a primary event in IBD or a phenomenon secondary to the inflammatory process. Noninflamed and inactively and actively inflamed mucosal tissues from patients with ulcerative colitis or Crohn's disease as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
257
2
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(281 citation statements)
references
References 45 publications
15
257
2
7
Order By: Relevance
“…Here, the altered ZO-1 (rather than ZO-2) mRNA levels that resulted from dietary proteins might be partly related to inflammation. Gassler et al [80] reported that in human intestinal inflamed mucosal tissues, ZO-1 gene expression was down-regulated, while the gene expression of ZO-2 was unaltered. This study found that low or high levels of protein triggered intestinal inflammation in young grass carp after infection with A. hydrophila.…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 99%
“…Here, the altered ZO-1 (rather than ZO-2) mRNA levels that resulted from dietary proteins might be partly related to inflammation. Gassler et al [80] reported that in human intestinal inflamed mucosal tissues, ZO-1 gene expression was down-regulated, while the gene expression of ZO-2 was unaltered. This study found that low or high levels of protein triggered intestinal inflammation in young grass carp after infection with A. hydrophila.…”
Section: General Summary: Optimal Dietary Protein Level Improve the Imentioning
confidence: 99%
“…25 Junctional proteins show reduced expression or changes in distribution in gut inflammation. [26][27][28] The dynamic nature of tight junctions is well demonstrated by the ability of cytokines and growth factors to modulate tight junction protein expression, regulate junction assembly and change epithelial permeability. [29][30][31][32][33] It has been established for many years that the cytokine profile of CD is T-helper type 1 and shows increased expression of the cytokines, TNFa and IFNg.…”
mentioning
confidence: 99%
“…The intestinal epithelium is considered a constitutive component of the mucosal immune system. Intestinal epithelial cells (IECs) are connected by tight junctions, which are dynamically regulated in response to cytokines and are down-regulated by the junctional complexes in human IBD (E-cadherin and β-catenin) [38] . The epithelium is in constant communication with luminal flora and the underlying network of innate and adaptive immune cells, and IECs constitutively express or can be induced to express costimulatory molecules [39] and components of the human major histocompatibility complex (MHC) [40] , toll-like receptors (TLRs) [41] , NOD proteins [42] , inflammatory cytokines [43] , as well as antimicrobial peptides [44] .…”
Section: Mucosal Epithelial Barrier Functionmentioning
confidence: 99%